Feasibility of magnetic resonance guided radiotherapy for the treatment of bladder cancer. (November 2020) - Hunt, A.; Hanson, I.; Dunlop, A.; Barnes, H.; Bower, L.; Chick, J.; Cruickshank, C.; Hall, E.; Herbert, T.; Lawes, R.; McQuaid, D.; McNair, H.; et al.
Highlights: Magnetic resonance image-guided whole bladder radiotherapy was feasible using a 1.5 T MR-linac. Each fraction was re-contoured, planned, and delivered in online workflow within 45 min. Intra-fraction bladder filling did not compromise target coverage. Abstract: Whole bladder magnetic resonance image-guided radiotherapy using the 1.5 Telsa MR-linac is feasible. Full online adaptive planning workflow based on the anatomy seen at each fraction was performed. This was delivered within 45 min. Intra-fraction bladder filling did not compromise target coverage. Patients reported acceptable tolerance of treatment.